THE TARA AND REFORESTATION CONDITIONS IN SAN JUAN MICROCUENCA(ALTO JEQUETEPEQUE) - Rojas Lazo, Oswaldo (2007)
Peru is the largest producer and exporter of dust tare, with the depatment of Cajamrca one of the first produsers. To increase their production, in recent years several reginal governments have given impetus to reforestation projects with this plant. In the province of Cajamrca, is located micro San Juan Basin, which is a revine which has 1400 families engaged in agriculture and animal husb andry staff, their land plots which are not allowed to be good income. In the year 2006, they collected 430 Tm fruit tare and the selling price of the quintal was S/.130 soles. from observations, we can say that it is technically feasible to reforest the micro basin with the tree tare, exist to do so close to 1500 hectares of arable land infertile and farming.